Application of Bacteriocins and Protective Cultures in Dairy Food Preservation - Silva, Célia C. G.; Silva, Sofia P. M.; Ribeiro, Susana C. (Frontiers in Microbiology, 2018)
In the last years, consumers are becoming increasingly aware of the human health risk posed by the use of chemical preservatives in foods. In contrast, the increasing demand by the dairy industry to extend shelf life and prevent spoilage of dairy products has appeal for new preservatives and new methods of conservation. Bacteriocins are antimicrobial peptides, which can be considered as safe since they can be easily degraded by proteolytic enzymes of the mammalian gastrointestinal tract. Also, most bacteriocin producers belong to lactic acid bacteria (LAB), a group that occurs naturally in foods and have a long history of safe use in dairy industry. Since they pose no health risk concerns, bacteriocins, either purified or excreted by bacteriocin producing strains, are a great alternative to the use of chemical preservatives in dairy products. Bacteriocins can be applied to dairy foods on a purified/crude form or as a bacteriocin producing LAB as part of fermentation process or as adjuvant culture. A number of applications of bacteriocins and bacteriocin-producing LAB have been reported to successful control pathogens in milk, yogurt and cheeses. One of the more recent trends consists in the incorporation of bacteriocins, directly as purified or semi-purified form or in incorporation of bacteriocin-producing LAB into bioactive films and coatings, applied directly onto the food surfaces and packaging. This review is focused on recent developments and applications of bacteriocins and bacteriocin-producing LAB for reducing the microbiological spoilage and improve safety of dairy products.